2017
DOI: 10.3168/jds.2016-12379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat content on the physical properties and consumer acceptability of vanilla ice cream

Abstract: Ice cream is a complex food matrix that contains multiple physical phases. Removal of 1 ingredient may affect not only its physical properties but also multiple sensory characteristics that may or may not be important to consumers. Fat not only contributes to texture, mouth feel, and flavor, but also serves as a structural element. We evaluated the effect of replacing fat with maltodextrin (MD) on select physical properties of ice cream and on consumer acceptability. Vanilla ice creams were formulated to conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 40 publications
6
38
0
4
Order By: Relevance
“…We also had to choose appropriate test stimuli that would generalize to real foods (vs. model systems) and appropriate behavioral methods. No one standard method has been adopted, with investigators in this area using many different stimuli to measure fat perception, including oil-and-water mixtures (Heinze et al 2017); oil in salad dressing (Keller et al 2012); fat in puddings (Mennella et al 2012), in scrambled eggs or mashed potatoes (Mela and Sacchetti 1991), or in ice cream (Rolon et al 2017) or added fatty acids in chocolate (Running et al 2017). Here we used potato chips that varied in amounts of corn oil and an added fatty acid, capitalizing on our technical expertise in their production and practical constraints of our testing environment (an annual convention of twins; see below).…”
Section: Introductionmentioning
confidence: 99%
“…We also had to choose appropriate test stimuli that would generalize to real foods (vs. model systems) and appropriate behavioral methods. No one standard method has been adopted, with investigators in this area using many different stimuli to measure fat perception, including oil-and-water mixtures (Heinze et al 2017); oil in salad dressing (Keller et al 2012); fat in puddings (Mennella et al 2012), in scrambled eggs or mashed potatoes (Mela and Sacchetti 1991), or in ice cream (Rolon et al 2017) or added fatty acids in chocolate (Running et al 2017). Here we used potato chips that varied in amounts of corn oil and an added fatty acid, capitalizing on our technical expertise in their production and practical constraints of our testing environment (an annual convention of twins; see below).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of low‐calorie product development studies, quality characteristics will be significantly affected by the type and level of substitute used. For example, Laura Rolon et al () found that maltodextrin usage rate and reduction in fat level resulted in a decrease in consumer acceptance of ice cream. Hyvönen et al () reported that the use of this component increases the rate of aroma release and melting in the fat‐free ice cream samples prepared by the use of maltodextrin at the level of 2.1%, and found that the perceived ‘fattiness’ and ‘creaminess’ properties become apparent.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity characteristics of ice cream mixtures change during the technological process under the influence of certain types of thermal and mechanical processing (mixing, pasteurization, homogenization, cooling, maturation, freezing) [1][2][3][4][5][6]. Thus, scientists at the University of Manchester (UK) have confirmed that the viscosity of ice cream mixtures is volatile and depends, first of all, on the temperature of the samples under study and the rate of shear [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocolloids and surfactants (stabilizers, emulsifiers and stabilization systems) are essential in the structuring of mixtures for the production of ice cream [5]. Equally important is the content of the fatty component, with the increase in the viscosity of the mixtures also rises [1][2][3][4][5][6][7], as well as its chemical composition and degree of conscientiousness. In the course of the latest developments, so-called "low-fat" milk fat substitutes such as starch, starch-lipid compositions, serum protein isolates (WPI), maltodextrins, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation